CYBER SECURITY SOLUTIONS FOR PROTECTING AND BUILDING THE FUTURE SMART GRID - Asija, Divya; Viral, R.K.; Daş, Resul; Tuna, Gurkan (Elsevier, 2024)
Cyber Security Solutions for Protecting and Building the Future Smart Grid guides the reader from the fundamentals of grid security to practical techniques necessary for grid defense. Through its triple structure, readers can expect pragmatic, detailed recommendations on the design of solutions and real-world problems. The book begins with a supportive grounding in the security needs and challenges of renewable-integrated modern grids. Next, industry professionals provide a wide range of case studies and examples for practical implementation. Finally, cutting-edge researchers and industry practitioners guide readers through regulatory requirements and develop a clear framework for identifying best practices. Providing a unique blend of theory and practice, this comprehensive resource will help readers safeguard the sustainable grids of the future. © 2025 Elsevier Inc. All rights are reserved.
Keywords: Blending; Cybersecurity; Network security; Case-studies; Cutting edges; Cyber security; Grid security; Industry professionals; Real-world problem; Regulatory requirements; Renewables; Security solutions; Smart grid; Smart power grids